Engaging in dialogue with Freire: on the pedagogical space and other shared reflections - Gutiérrez Slon, Juan Antonio; Vargas Vargas, Bryan (Innovaciones Educativas, 2022)
The essay emphasizes some of Paulo Freire’s reflections based on the analysis of “education as a practice of freedom” in the light of three of his works: one theoretical, one empirical approach, and one of synthesis. It emphasizes discussions on the condition of oppression that is framed in the educational processes while investigating the author’s methodological perspective on the pedagogical domain and the possibilities it has to overcome the oppressor-oppressed relationship with a proposal of problematization based on the actual voices without discrimination included in the educational processes of the socio-political world.